2021
DOI: 10.1113/jp281657
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interplay between AfadinS1795 phosphorylation and diet regulates glucose homeostasis in obese mice

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…As recently discussed [ 28 ], a large part of the stress response likely comes from manipulating the tail to collect blood, and therefore GTT procedures in which smaller blood samples are taken may reduce stress-induced rises in blood glucose. We report that insulin can be reliably measured from small (as low as 5 μl) samples of blood by ELISA (as measured in previous publications [ 35 , 36 ]). Whole blood insulin shows a strong linear correlation with plasma insulin ( Figure 4 A) at both low and high concentrations ( Figure 4 B) with whole-blood insulin values recorded as ∼70% of plasma values ( Figure 4 C) likely due to dilution of insulin in whole-blood by the non-plasma fraction.…”
Section: Resultsmentioning
confidence: 55%
“…As recently discussed [ 28 ], a large part of the stress response likely comes from manipulating the tail to collect blood, and therefore GTT procedures in which smaller blood samples are taken may reduce stress-induced rises in blood glucose. We report that insulin can be reliably measured from small (as low as 5 μl) samples of blood by ELISA (as measured in previous publications [ 35 , 36 ]). Whole blood insulin shows a strong linear correlation with plasma insulin ( Figure 4 A) at both low and high concentrations ( Figure 4 B) with whole-blood insulin values recorded as ∼70% of plasma values ( Figure 4 C) likely due to dilution of insulin in whole-blood by the non-plasma fraction.…”
Section: Resultsmentioning
confidence: 55%
“… 133 Phosphorylation of Afadin at S1795 also promotes insulin resistance in the early stages of diet‐induced obesity. 134 …”
Section: Phosphorylationmentioning
confidence: 99%
“…In addition, phosphorylation of obesity‐associated PPARγ at S273 induces insulin resistance by upregulating Gdf3 expression and inhibiting the BMP signaling pathway1 133 . Phosphorylation of Afadin at S1795 also promotes insulin resistance in the early stages of diet‐induced obesity 134 …”
Section: Phosphorylationmentioning
confidence: 99%
“…Afadin phosphorylation alters Adherens Junctions in kidney epithelial cells and favours cell migration of breast cancer cells (Elloul et al, 2014;Gao et al, 2017). Of note, it has been suggested that Afadin phosphorylation may also be involved in the negative feed-back regulation of insulin action in adipocytes (Lundh et al, 2019), and Afadin phospho-mutant mice display a mild amelioration of glucose homeostasis at the early stages of high fat diet (Tozzi et al, 2022). Consistent with an important role of the mTOR/S6K1 pathway on cell adhesion, S6K1 phosphorylation down-regulates PI 4 phosphate 5 kinase type I g (PIPKIg90), which mediates together with talin the assembly of focal adhesion (Jafari et al, 2016).…”
Section: Cytoskeleton Dynamicsmentioning
confidence: 99%